Analysis of Legal Voids in the Implementation of Public Private Partnerships as a Model for Financing Infrastructure Projects in Indonesia - Tiawarman K., Andriansyah; Vic , Binsar Jon (Devotion : Journal of Research and Community Service, 2025)
Public Private Partnership (PPP) has become a vital model for financing infrastructure development in Indonesia, addressing the limitation of state budget resources. However, the implementation of this model faces significant challenges due to legal voids and unclear regulations, leading to uncertainty and inefficiencies in infrastructure projects. This study aims to identify and analyze the legal gaps in the PPP framework, assess their impact on the cooperation process between the government and the private sector, and evaluate efforts by the government to address these gaps. Utilizing a normative legal approach and case study analysis, the research explores existing legal norms, identifies inconsistencies in regulations, and examines their effects on PPP project outcomes. The findings highlight the lack of synchronized regulations, unclear risk allocation, and gaps in contract termination and dispute resolution mechanisms. These issues contribute to investor hesitation and project delays. The study concludes that comprehensive regulatory reforms, including the establishment of a unified PPP law and clearer risk-sharing mechanisms, are necessary to create a more conducive investment climate and enhance the effectiveness of PPPs in infrastructure development. This research offers practical recommendations to improve legal certainty and policy implementation for future PPP projects in Indonesia.